1985
DOI: 10.1099/00221287-131-10-2759
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NAD Biosynthesis in Salmonella typhimurium: Expression of nad--lac Gene Fusions and Identification of a nad Regulatory Locus

Abstract: Regulation of NAD biosynthesis was examined through the construction of nad-lac fusions in Salmonella typhimurium. The nadA (17 unit map position) and nadB (55 units) genetic loci involved with quinolinic acid biosynthesis were both found to be regulated by the product of a nadR locus (99 units) in a repression/derepression manner while nadC (3 units) expression appeared constitutive at the transcriptional level. Increases in nadAB transcription directly correlated with decreases in intracellular NAD(P) levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Previous work has demonstrated that mutants defective in both repression and NMN transport map at a single locus (nadl) on the Salmonella chromosome (10,17,20,30,50 (ii) We provide evidence that the activity of this transport system does in fact vary in response to cell physiology, The regulatory signal is likely to be NAD or NADP, since nadE mutants (blocked ih NAD synthetase) are unable to vary NMN transport activity in response to exogenous NA. Mutations that limit nadE function also cause increased transcription of biosynthetic genes, suggesting that NAD (or NADP) is also the effector for the repressor activity of the NadI protein (23).…”
Section: Discussionmentioning
confidence: 80%
“…Previous work has demonstrated that mutants defective in both repression and NMN transport map at a single locus (nadl) on the Salmonella chromosome (10,17,20,30,50 (ii) We provide evidence that the activity of this transport system does in fact vary in response to cell physiology, The regulatory signal is likely to be NAD or NADP, since nadE mutants (blocked ih NAD synthetase) are unable to vary NMN transport activity in response to exogenous NA. Mutations that limit nadE function also cause increased transcription of biosynthetic genes, suggesting that NAD (or NADP) is also the effector for the repressor activity of the NadI protein (23).…”
Section: Discussionmentioning
confidence: 80%
“…The bacteriophages M13mpl8 and M13mpl9 were used for some of the sequencing studies. Cultural conditions were as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty minutes after the addition of rifampin, the cells were pulse labeled for 5 min with 10 ,uCi of [35S]methionine per ml. Cells were harvested by centrifugation, washed with an equal volume of ice-cold E buffer (8), and then stored at -70°C. Crude membranes were prepared by suspending labeled cells in 300 ,u1 of sonication buffer (100 mM Tris hydrochloride, 50 mM MgCl2, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations